Optimizing School Health With An Integrated Information System: A Case Study At Man Insan Cendekia Sorong - Wahyu Hidayat M; Muhammad Sadidan; Al Hikma Sake; Della Fadhilatunisa (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
The task of schools is to develop the whole person and provide effective knowledge and education. In the UKS MAN Insan Cendekia Sorong, the main problem obtained is the processing and data collection that is still done manually so that it can cause patient services to be limited, less effective and efficient. The solution to solve this problem is to build a school health information system that helps school health workers in managing data about UKS. Data collection methods are carried out using questionnaires, interviews and observations. The system development method used is waterfall. chosen because it is easy to implement and the resources required are minimal. This school health information system for UKS allows the management of patient data, drug data, and patient medical records to be organised and efficient.